Implementation of Computer Assisted Instruction Media to Improve Understanding of English Education Materials In SMA Subang - Ida Maulida (Institute of Computer Science (IOCS), 2022)
Computer Assisted Instruction (CAI) is a learning aid media that places the computer as an individual learning system device, where students can interact directly with computer applications and is designed to improve students' ability to understand the various subject matter that has been conveyed. CAI-based learning is able to bring a new atmosphere when the teaching and learning process is being carried out in the classroom. This study aims to develop and evaluate the Computer Assisted Instruction method that was developed through English subjects, while the research method used was development research through the results of field tests. So the results of this study explain that the product development of English teaching materials based on Computer Assisted Instruction (CAI) in improving student learning outcomes in the high school environment of Subang Regency is carried out by analyzing and developing these products starting from the instructional design stage, one-on-one test. one, small group test and field test results using students' pretest and posttest calculations, the feasibility of the Computer Assisted Instruction method got a positive response from all students and teachers, because the media helped students understand various English subject matter and was able to stimulate the mind, feelings, concerns and abilities or skills of students so that there are significant differences in student learning outcomes before and after using CAI media. In other words, CAI media for learning English is considered effective and can improve overall student learning outcomes.